Phase II study of carfilzomib and dexamethasone therapy for newly diagnosed multiple myeloma. Issue 5 (25th February 2019) - Forsberg, Peter A.; Rossi, Adriana C.; Boyer, Angelique; Tegnestam, Linda; Pearse, Roger N.; Perry, Arthur; Pekle, Karen A.; Jayabalan, David; Ely, Scott; Boussi, Leora; Sherbenou, Daniel W.; Williams, Colt; et al.
Abstract : Carfilzomib and dexamethasone (Kd) has significant activity in relapsed and refractory multiple myeloma. Kd has not previously been evaluated in newly diagnosed multiple myeloma (NDMM). We report a single‐arm phase 2 study of 72 patients with NDMM to evaluate the efficacy and tolerability of Kd induction. Carfilzomib was administered in two dosing cohorts with dosing of 20/45 mg/m 2 in the first 25 patients and 20/56 mg/m 2 in the subsequent 47 patients. Carfilzomib was administered on days 1, 2, 8, 9, 15 and 16 of a 28‐day cycle, dexamethasone 20 mg was administered orally on days 1, 2, 8, 9, 15, 16, 22 and 23. Treatment was continued to maximum response, progression of disease, or regimen intolerability. Endpoints included overall response rate (ORR), regimen toxicity and impact of carfilzomib on CD34+ stem cell collection yield. Sixty‐five pts achieved at least a partial response (PR) for an ORR of 90%. The maximum response achieved was complete response or better in 5 (7%), very good partial response (VGPR) in 42 (58%), PR in 18 (25%) and stable disease in 7 pts (10%). Toxicities were predominantly low grade with 547 grade 1/2 adverse events and 44 grade ≥3 events. The rate of grade ≥3 cardiovascular adverse events was 11.1% with eight observed events. The activity of Kd described represents the highest rate of overall response and ≥VGPR for any 2‐agent combination in NDMM reported to date. Kd demonstrated a safety profile consistent with previously reported carfilzomib studies.